The potential role of economic instruments in river basin management: increased economic efficiency through paying farmers to use less water - Ringler, Claudia (Oekom Publishers GmbH, 2007)
Better rules for sharing water could make a large difference for equity and productivity outcomes. Economic incentives for water management, including prices, taxes, subsidies, quotas, and use or ownership rights can affect the decisions of water users and motivate them to conserve and use water more efficiently.